Inappropriate Behavior in Buying and Selling Usernames on Twitter: An Islamic Law Perspective - Nizami, Auliya Ghazna; Andini Rahma Hidayah; Hidayatulloh (Jurnal Hukum Islam, 2023)
Transformations in the digital world allow illicit transactions such as buying and selling usernames, which are currently popular among social media users, especially on Twitter. The more people who use Twitter, the more usernames are used, and the system will automatically reject new user requests with usernames that have already been used. This research examined username buying and selling transactions and inappropriate behavior by users on Twitter. This research used qualitative methods with an approach to Islamic legal norms. Data were obtained from document studies and interviews with sellers and buyers of usernames via Twitter direct messages. The results of the research showed that buying and selling usernames are an illegal and prohibited sale because many inappropriate behaviors, such as hacking, are found, resulting in nonfulfillment of the conditions for the objects bought and sold. Islamic law stipulates that traded objects must meet requirements such as perfect ownership, clear, useful, and halal. This means that there is no element of gharar in every buying and selling transaction because it can cause disputes between the seller and the buyer.